2021
DOI: 10.3390/molecules26144295
|View full text |Cite
|
Sign up to set email alerts
|

Ziziphus nummularia Attenuates the Malignant Phenotype of Human Pancreatic Cancer Cells: Role of ROS

Abstract: Pancreatic cancer (PC) is the fourth leading cause of all cancer-related deaths. Despite major improvements in treating PC, low survival rate remains a major challenge, indicating the need for alternative approaches, including herbal medicine. Among medicinal plants is Ziziphus nummularia (family Rhamnaceae), which is a thorny shrub rich in bioactive molecules. Leaves of Ziziphus nummularia have been used to treat many pathological conditions, including cancer. However, their effects on human PC are still unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Based on the US National Cancer Institute (NCI) guidelines, a crude extract is generally considered to have high in vitro cytotoxic activity if the IC 50 value is ≤ 30 μg/mL [ 37 , 38 ]. Pezzuto et al consider extracts with higher IC 50 values (100 μg/mL) to be cytotoxic and eligible candidates for further studies [ 39 ], while several recently published papers [ 40 , 41 , 42 , 43 , 44 , 45 ] explore the biological activity of plant extracts with IC 50 values higher than 200 μg/mL. Importantly, all the extracts made from the whole fruit using EA and DE induced apoptosis in MCF-7 cells with no significant effects on the normal breast cell line MCF-10A.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the US National Cancer Institute (NCI) guidelines, a crude extract is generally considered to have high in vitro cytotoxic activity if the IC 50 value is ≤ 30 μg/mL [ 37 , 38 ]. Pezzuto et al consider extracts with higher IC 50 values (100 μg/mL) to be cytotoxic and eligible candidates for further studies [ 39 ], while several recently published papers [ 40 , 41 , 42 , 43 , 44 , 45 ] explore the biological activity of plant extracts with IC 50 values higher than 200 μg/mL. Importantly, all the extracts made from the whole fruit using EA and DE induced apoptosis in MCF-7 cells with no significant effects on the normal breast cell line MCF-10A.…”
Section: Discussionmentioning
confidence: 99%
“…Although low levels of ROS can be beneficial, excessive accumulation can promote cancer [11]. It is becoming increasingly evident that ROS play crucial roles in the survival, proliferation, invasion, angiogenesis, and metastasis of tumor cells [12][13][14]. Under normal conditions, ROS production is balanced by ROS scavenging through the antioxidant defense machinery, resulting in redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The same extract was also able to attenuate angiogenesis by reducing the production of secreted and intracellular vascular endothelial growth factor (VEGF), a pro-angiogenic protein, as well as the levels of nitric oxide. This anti-angiogenic effect was further confirmed by in ovo experiments using the chick embryo chorioallantoic membrane assay [81]. These studies have shown that Ziziphus nummularia extracts and the isolated compounds described above exhibit strong anticancer activities against various types cancers and target the hallmarks of cancer.…”
Section: Anticancer Activitymentioning
confidence: 61%
“…In another study, the methanolic fruit extract of Ziziphus nummularia showed appreciable cytotoxic activity against cervical carcinoma cells, HeLa cells [58]. Furthermore, the ethanolic extract from Ziziphus nummularia leaves was shown to inhibit the hallmarks of pancreatic cancer by interfering with tumorigenic and metastatic events [81]. Indeed, treatment of capan-2 pancreatic cancer cells resulted in an attenuation of cell proliferation and a significant decrease in their migration and invasion potentials.…”
Section: Anticancer Activitymentioning
confidence: 99%